(untitled) (Research, Society and Development, 2022)
Objective: To retrieve scientific evidence on pharmaceutical services related to the treatment of Covid-19. Methodology: Integrative Review, with a time frame from 2020 to 2022. Results: Sixteen studies were retrieved from different regions of the world: Brazil (3), China (3), Egypt (1), United Kingdom (1), Kosovo (1), United Arab Emirates (1), Poland (1), Czech Republic (1), Portugal (1), Jordan (1) and Lebanon (1). It is observed that the studies do not report in depth issues related to equity, such as location, race, occupation, sex, religion, education, social capital and economic status. Conclusion: The prevention and treatment of Covid-19 have an intrinsic link with pharmaceutical care through the provision of pharmaceutical services, such as the pharmaceutical care performed by the pharmacist. The pandemic has brought with it changes and advances in health that promote the dissemination of active/passive, face-to-face/remote information, such as telepharmacy guidance services; one of the main means of disseminating knowledge about the rational use of medicines, based on scientific evidence on the prophylaxis and treatment of Covid-19.